Sustainable Materials - Rivera-Armenta, Jose Luis; Kolisnychenko, Stanislav (Trans Tech Publications, 2023)
This book, a review of the latest trends in the practice of production and synthesis of various types of materials on principles of sustainability, contains articles published by Trans Tech Publications Inc. in the last few years. The edition will be helpful and interesting to a broad audience of specialists in materials science.